Hybridization of Nanoclay with a Chromium‐Based Metal‐Organic Framework for Boosting Adsorption of Organic Dyes from Wastewater. Issue 5 (1st February 2022) - Far, Hossein Shahriyari; Hasanzadeh, Mahdi; Najafi, Mina; Rahimi, Rahmatollah
Abstract: We demonstrate enhanced dye adsorption capacity of nanoclay by decoration with chromium‐based MOF (MIL‐101) nanostructure. The Clay/Cr‐MOF composite exhibits a crystalline structure with high thermal stability. Moreover, it shows the superior specific surface area (4959 m 2 /g) and porosity which is beneficial for wastewater treatment. The developed Clay‐MOF composite exhibits superb adsorption capacity toward various organic dyes as compared with existing materials. The adsorption experiments revealed high adsorption capacity and selective dye removal efficiency of MOF‐modified nanoclay with reusability for multiple regeneration cycles. The adsorption kinetics was found to obey the pseudo‐second‐order kinetic model. These findings provide new insights into the application of such porous adsorbents for wastewater treatment applications. Abstract : A highly efficient Clay‐MOF composite for adsorption of organic dyes from wastewater was successfully prepared. The composite is comprised of chromium‐based MOF nanocrystals which are in‐situ grown on nanoclay structure. The Clay/Cr‐MOF composite exhibits high adsorption capacity and selective dye removal, thanks to their superior specific surface area and porosity. The designed composite could be used as an efficient adsorbent for wastewater treatment.